The major integration features of banking system - Mirhashimli Leyla; Hasanova Afag; Choriev A. (BIO Web of Conferences)
The internationalization of the banking sector in developing countries brings both significant benefits and challenges. Foreign banks promote competition, efficiency and financial inclusion, which accelerates the integration of local banking systems into the global economy. However, the arrival of large international players may increase risks and force local banks to make significant changes. Studies show that the influence of foreign banks is ambiguous and depends on the level of economic development of the country. When assessing the effects of globalization, it is important to consider the differences between developed and developing countries. In periods of economic crisis, foreign banks can play a stabilizing role, but they can also import shocks from their own countries. To maximize benefits and minimize risks, it is necessary to develop a strategy that ensures a balanced presence of foreign banks, supports competition and innovation, but does not allow excessive concentration of bank capital. In this context, the internationalization of financial services becomes an important tool for strengthening and liberalizing the financial systems of developing countries, opening new opportunities for their economic growth and sustainable development. Since the collapse of the Bretton Woods system and the beginning of the era of financial liberalization, one of the most important manifestations of the process of integration of the banking sector into the world economy has been the expansion of foreign banking capital into foreign markets. Financial sector liberalization is intended to provide equal opportunities for financial institutions to access the international market or reduce restrictions from local regulators. Liberalization of the banking industry is one of the most important financial sector liberalization programs.